Impacts of heterogeneous reactions to atmospheric peroxides: Observations and budget analysis study - M.R. Qin; Chen, Z. M.; H.Q. Shen; H. Li; H.H. Wu; Y. Wang (Atmospheric Environment, 2018)
Atmospheric peroxides play important roles in atmospheric chemistry, acting as reactive oxidants and reservoirs of HOx and ROx radicals. Field measurements of atmospheric peroxides were conducted over urban Beijing from 2015 to 2016, including dust storm days, haze days and different seasons. We employed a box model based on RACM2 mechanism to conduct concentration simulation and budget analysis of hydrogen peroxide (H2O2) and peroxyacetic acid (PAA). In this study, heterogeneous reaction is found to be a significant sink for atmospheric H2O2 and PAA in urban Beijing. Here, we recommend a suitable uptake coefficient formula considering the water effect for model research of peroxides. It is found that H2O2 and PAA unexpectedly maintained considerable concentrations on haze days, even higher than that on non-haze days. This phenomenon is mainly ascribed to relatively high levels of volatile organic compounds and ozone on haze days. In addition, high levels of water vapor in pollution episode can promote not only the heterogeneous uptake to aerosol phase but also the production of H2O2. Atmospheric PAA formation is suggested to be sensitive to alkenes and NOx in urban Beijing. In particular, with the help of peroxides, sulfate formation rate from heterogeneous uptake could increase by ∼4 times on haze days, indicating the potential effect of peroxides on enhancement of aerosol oxidative property and secondary sulfate formation.